Streptozotocin - an antibiotic used to induce diabetes on experimental animals - Dagna Siedlecka; Wojciech Micał; Ewa Krzewicka-Romaniuk (Kazimierz Wielki University, 2020)
Streptozotocin (STZ) is a cytostatic antibiotic produced by Streptomyces achromogenes. It is an inhibitor of DNA replication showing a special affinity for pancreatic β-cells DNA. It is used in medicine as an antineoplastic agent (indicated in the treatment of malignant neoplasms of pancreas) and in scientific research to induce hyperglycemia, insulitis, diabetes mellitus (DM), Alzheimer's disease on experimental animals. Insulinopenia syndrome is called 'streptozotocin diabetes', caused by necrosis of the pancreatic β-cells. STZ induced DM offers a very cost-effective and expeditious technique in medical research.